The Effect of Entrepreneurship Education and Technological Advancement on the Entrepreneurial Intention - Alicia Megawati; Yohana, Corry; Zakiah, Rizka (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to determine the effect of entrepreneurship education and technological advancement in influencing the entrepreneurial intention of vocational high school students (SMK) in Jakarta. Entrepreneurial intention is a desire from within a person that is formed from a mindset to create a business that is beneficial to oneself and others with innovation and creativity. Entrepreneurial intention needs to be increased considering the need to increase young entrepreneurs and to reduce unemployment in Indonesia, especially Jakarta. The phenomenon of entrepreneurship education and technological advancement that should support business learning opportunities to increase entrepreneurial intention, does not seem to be able to fully increase students’ entrepreneurial intention. This research was conducted in Jakarta using a quantitative approach with a descriptive and correlational approach. The data used is primary data obtained by distributing questionnaires. The analysis method uses multiple linear regression analysis, validity and reliability tests, classical assumption tests and hypothesis testing using the SPSS version 29 application. The research sample was 200 vocational students in Jakarta using non-probability sampling techniques and purposive sampling. This research answers that Entrepreneurship Education effect the Entrepreneurial Intention,Technological Advancement effect the Entrepreneurial Intention, and Entrepreneurship Education and Technological Advancement effect the Entrepreneurial Intention